Localization Using Magnetic Patterns for Autonomous Mobile Robot. (27th March 2014) - You, Won Suk; Choi, Byung June; Choi, Hyouk Ryeol; Koo, Ja Choon; Moon, Hyungpil
In this paper, we present a method of localization using magnetic landmarks. With this method, it is possible to compensate the pose error ( x e, y e, θ e ) of a mobile robot correctly and localize its current position on a global coordinate system on the surface of a structured environment with magnetic landmarks. A set of four magnetic bars forms total six different patterns of landmarks and these patterns can be read by the mobile robot with magnetic hall sensors. A sequential motion strategy for a mobile robot is proposed to find the geometric center of magnetic landmarks by reading the nonlinear magnetic field. The mobile robot first moves into the center region of the landmark where it can read the magnetic pattern, after which tracking and global localization can be easily achieved by recognizing the patterns of neighboring landmarks. Experimental results show the effectiveness of the sequential motion strategy for estimating the center of the first encountered landmark as well as the performance of tracking and global localization of the proposed system.